Pilot-scale multi-stage reverse osmosis (DT-RO) for water recovery from landfill leachate. (June 2018) - Cingolani, D.; Fatone, F.; Frison, N.; Spinelli, M.; Eusebi, A.L.
Graphical abstract: Highlights: Tertiary treatment of landfill leachate was studied by DT-RO in full-scale field. Water recovery was higher than 91% by combining two RO stages. Boron concentration lower than 2 mg/L met the standard for water reuse. Ions and metals rejections were assessed in each single RO stage. Combined evaluation of Δπ and ΔP can support the decision of optimal operation. Abstract: Recovery of high quality water from municipal landfill leachate was studied by three-stage disc tube reverse osmosis optimized in pilot-scale. Following UF-membrane-assisted activated sludge plant, overall 46.5 tons of leachate were post-treated in real environment and analyzed for conventional contaminants and hazardous compounds (e.g. heavy metals, boron, selenium) throughout operation of membrane system. Operating pressure ranged from 21 to 76 bar, while permeate flux varied in the range 7.1–32.5 L m −2 h −1 . Rejection factors of specific ions were related to the pressure and global removals were assessed for each stage (e.g. E%COD = 92.4–99.2%, E%NH4 = 46.2–95.8%, E%NOx = 84.8–97.9%; E%TDS = 88–95.5%). Boron removal was assessed in the range 34–48%, so as to require the third stage to reach standard for discharge or reuse. Two stages were sufficient to reach water recovery higher than 91%. Long-term operation and mathematical modeling demonstrated how the Δπ/ΔP ratio can support the decisions for membrane cleaning and predictive maintenance: permeability decline was associated to the ratio increase from 0.72 to 0.73 to 1.13–1.21.